Study about Fostering Autonomous Language Learners in a Japanese University - Mayumi Kanazawa (Current Research in Language, Literature and Education Vol. 2, 2021)
This study aims to find out whether incorporating ‘self-study’ in the course syllabus fosters learners’ autonomous learning, one of the most important factors in the field of language acquisition. Leaning a language demands a considerable amount of time and learners have to work within and outside the classroom to develop their language skills. The present study explored ways of promoting autonomous learning skills in a classroom in mixed-level students of English at a Japanese university. The course syllabus, which employed various methods was developed in order to increase students’ autonomous learning skills and incorporate a self-study period during the semester. The students set their own goals, then planned, developed and followed strategies to achieve them. Learners also kept a weekly learning-log, culminating in a presentation and a written report about what they had done to achieve their goals, including self-evaluation. The results showed that the students recognized some improvements in their English learning skills, motivation and learning habits, including an increase in learning hours. In addition, the students gained confidence in their English learning. Further practical improvements are suggested for supporting students to become autonomous language learners.